(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article explores effective pedagogical approaches for teaching writing to English as a Foreign Language (EFL) learners, addressing the inherent challenges they face with this complex skill. It argues that successful writing instruction moves beyond traditional grammar-focused methods to foster confident and articulate communicators. Key strategies discussed include demystifying the writing process by breaking it into manageable stages (brainstorming, outlining, drafting, revising, editing) and providing students with clear purposes and defined audiences for their writing tasks. The article emphasizes the critical role of constructive feedback, advocating for targeted teacher input and the significant benefits of structured peer feedback in fostering critical thinking and self-correction. Furthermore, it highlights the invaluable contribution of technological tools in enhancing student engagement, providing authentic materials, and facilitating collaborative learning experiences. Ultimately, the article concludes that by cultivating a supportive environment that encourages experimentation and views mistakes as learning opportunities, educators can empower EFL students to overcome writing apprehension and develop strong, effective writing skills for real-world communication.